Effect of perioperative methylprednisolone administration on postoperative pleural effusion in older patients with non-small cell lung cancer - Xinyu Hao; Yongxin Guo; Ziyao Xu; Yanping Song; Jingjing Liu; Likai Shi; Qiang Fu; Wenzhu Shi; Jiangbei Cao; Yanhong Liu; Li Tong; Weidong Mi (BMC Anesthesiology)
Abstract Background It remains uncertain whether the utilization of methylprednisolone during surgery effectively mitigates the occurrence of adverse outcomes. To examine the association between perioperative methylprednisolone administration and postoperative pleural effusion and pneumonia in older patients with non-small cell lung cancer. Methods A retrospective cohort study included non-small cell lung cancer patients aged 65 years or older undergoing thoracic surgery between January 2012 and December 2019 in China. Primary outcome was pleural effusion. Secondary outcome was postoperative pneumonia. Multivariate logistic regression models assessed the independent effects of various factors on pleural effusion and pneumonia. Propensity score matching (PSM) method reduced selection bias enhancing causal inference validity. Subgroup analyses identified potential effect heterogeneity in specific sub-populations. Results A total of 1951 older patients with non-small cell lung cancer were included. The incidence of postoperative pleural effusion in the methylprednisolone group before and after PSM matching was significantly lower than that in the control group (before PSM: 9.4% vs. 19.2, P < 0.001; after PSM: 9.8% vs. 18.2%, P < 0.001). There was no statistically significant difference in the incidence of postoperative pneumonia between the two groups before and after matching. After adjusting all the variables and PSM, we found that intraoperative methylprednisolone was associated with a reduction in postoperative pleural effusion in older patients with non-small cell lung cancer [odds ratio (OR) = 0.48, P < 0.001; OR = 0.47, P < 0.001]. Perioperative methylprednisolone showed consistent protective effects in all sub-populations of gender, age, surgery duration, and smoking (P all < 0.05). Logistic regression models and PSM found that methylprednisolone was not associated with postoperative pneumonia and long-term survival in older patients with non-small cell lung cancer. Conclusion Perioperative methylprednisolone was associated with reducing the occurrence of postoperative pleural effusions in older patients with non-small volume lung cancer, but it was not associated with pneumonia or long-term survival outcomes.